Scientific outreach in astronomy for children in the pandemic context: a proposal for an elective course for the pedagogy degree - Amorim, Vitor; Belli, Giselli; Izidoro, Emerson; Vieira, Rui Manoel de Bastos (Cadernos de Astronomia, 2024)
This article describes an experience developed in the context of an elective course, Scientific Outreach in Astronomy for Children, offered virtually to Pedagogy students at the Federal University of São Paulo (Unifesp) during the second semester of 2021, due to the Covid-19 pandemic. The course covered basic Astronomy concepts to strategies for video production for scientific outreach, facing challenges in the transition from in-person to remote education. The didactic methodology included dividing the course syllabus into three blocks, addressing essential topics for Astronomy Education, and emphasized the flexibility and resilience required in the virtual environment. The course's objectives, such as providing theoretical and practical training, discussing relevant topics for Astronomy Education, and studying proposals for scientific outreach practices, were achieved. The collaborative approach and practical activities stimulated students' critical and scientific thinking, contributing to considering Scientific Outreach as a didactic possibility within science education. The experience reinforced the importance of communication and language in the educational process, even at a distance, and the need to explore technological tools in a creative and efficient manner.
Keywords: scientific education; teacher training; audiovisual production